Implementation of The Lake Paisu Pok Tourism Development Policy (Challenges and Recommendations for Enhancing Tourist Attraction): Implementasi Kebijakan Pengembangan Pariwisata Danau Paisu Pok (Tantangan dan Rekomendasi untuk Meningkatkan Daya Tarik Wisata) - Kurnia, Intam; Irfan, Muhammad; Intan Kumbayoni, Ni Gusti Putu; Fiki Ferianto; Ruliyanti; Badollahi, Muh. Zainuddin (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2024)
This research aims to analyze the implementation of the flagship tourism development policy at Lake Paisu Pok. The research method used is a case study with a qualitative approach. Data were collected through in-depth interviews with various stakeholders, field observations, and documentary studies. The results of the research indicate that the implementation of the flagship tourism development policy at Lake Paisu Pok has achieved several achievements but still faces several challenges, such as a lack of supporting infrastructure, suboptimal coordination among relevant agencies, and ineffective tourism promotion and marketing. Based on these findings, it is recommended that local governments and various stakeholders improve coordination and cross-sectoral cooperation, enhance supporting infrastructure, and improve tourism promotion and marketing to enhance Lake Paisu Pok's attractiveness as a flagship tourism destination.